Benchmarking a fast and simple on-site detection assay for the oak wilt pathogen Bretziella fagacearum - Bourgault, Émilie; Gauthier, Marie-Krystel; Potvin, Amélie; Stewart, Don; Chahal, Karandeep; Sakalidis, Monique L.; Tanguay, Philippe (Frontiers in Forests and Global Change, 2022)
Oak wilt is a vascular disease of oak trees caused by the fungus Bretziella fagacearum. Once infected, trees may die in a few weeks. Although the disease is currently only found in the United States, it has been reported within just a few hundred meters of the Canada-USA border. To limit the establishment and spread of oak wilt in Canada, the development of an on-site, quick and reliable method to detect B. fagacearum is critical. In this study, we developed and validated a new qPCR TaqMan® assay that can detect B. fagacearum in a laboratory setting with great specificity and sensitivity. Using this test as a reference, we also developed and validated a new DETECTR assay that can detect B. fagacearum under one hour from a variety of environmental samples, such as mycelium mats and insect vectors, using minimal laboratory equipment. While there are still some limitations to the sensitivity of this assay, we believe that its ease of use, flexibility and accuracy will provide an essential tool in efforts to reduce the spread of oak wilt.